Hub Genes Identification in a Murine Model of Allergic Rhinitis Based on Bioinformatics Analysis - Chen, Le; Shi, Le; Ma, Yue; Zheng, Chunquan (Frontiers in Genetics, 2020)
This study aimed to identify allergic rhinitis (AR) related hub genes and functionally enriched pathways in a murine model. Dataset GSE52804 (including 3 normal controls and 3 AR mice) was downloaded from Gene Expression Omnibus (GEO). Differentially expressed genes (DEGs) were identified. Gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, and protein-protein interaction (PPI) analyses of DEGs were performed to identify the hub genes in AR. The DEGs were classified into different modules by using the weighted gene co-expression network analysis (WGCNA). Moreover, to verify the potential hub genes, nasal mucosa tissues were obtained from murine AR models (n=5) and controls (n=5), and qRT-PCR and western blot were performed. In this study, a total of 634 DEGs were identified. They were significantly enriched in 14 GO terms, such as integral component of membrane, plasma membrane, and G-protein coupled receptor signaling pathway. Meanwhile, there were 8 terms of KEGG pathways significantly enriched, such as Olfactory transduction, Cytokine-cytokine receptor interaction, and TNF signaling pathway. The top 10 hub genes (Rtp1, Rps27a, Penk, Cxcl2, Gng8, Gng3, Cxcl1, Cxcr2, Ccl9, Anxa1) were identified by PPI network. DEGs were classified into 7 modules by WGCNA. According to qRT-PCR validation of the five genes of interest (Rtp1, Rps27a, Penk, Cxcl2, and Anxa1), the expression level of Rtp1 mRNA was significantly decreased in AR group compared with the control group, while there are enhanced Rps27a, Penk, Cxcl2 and Anxa1 mRNA expressions in AR mice group compared with the control group. Western blot was also performed to further explore the expression of Anxa1 in protein level and the results showed a similar expression trend.